2021
DOI: 10.1038/s41598-021-00758-w
|View full text |Cite
|
Sign up to set email alerts
|

Internal morphology of 101 mandibular canines of a Swiss-German population by means of micro-CT: An ex vivo study

Abstract: The aim of this study was to investigate the root canal system morphology by means of a root canal configuration (RCC) classification described with a four-digit system, the physiological foramen geometry and accessory canal frequency and morphology, of 101 mandibular canines (MaCa) of a Swiss-German population by means of micro-computed tomography. Micro-CT examination of the MaCa was performed and the obtained images analyzed with a 3D imaging software. In single-rooted MaCas, the most frequently observed RC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
2
1
Order By: Relevance
“…Our findings are inconsistent with a study by Wolf et al in the German population, in which type I was presented as 74.5%, followed by 14.3% for the type II class. 84 These results differed from other studies, in which type I prevalence was reported as 81.5% in the Mexican population, 1 80.4% in the Turkish population, 66 95.4% in the Hamadani population in Iran, 85 and 92% in the South Asian Indian population. 83 These differences in RMCC can be attributed to racial differences in patients even within the same population, which is considered an important factor that can affect clinicians' perceptions of anatomical suspicion about RMCCs.…”
contrasting
confidence: 59%
“…Our findings are inconsistent with a study by Wolf et al in the German population, in which type I was presented as 74.5%, followed by 14.3% for the type II class. 84 These results differed from other studies, in which type I prevalence was reported as 81.5% in the Mexican population, 1 80.4% in the Turkish population, 66 95.4% in the Hamadani population in Iran, 85 and 92% in the South Asian Indian population. 83 These differences in RMCC can be attributed to racial differences in patients even within the same population, which is considered an important factor that can affect clinicians' perceptions of anatomical suspicion about RMCCs.…”
contrasting
confidence: 59%
“…The results of the current investigation demonstrated a relatively high percentage 21% for an overall two-root canals anatomy in mandibular canines in this Egyptian subpopulation compared to other CBCT studies on different populations, where a study on 200 Iranian subjects showed overall 2.4% for a second canal 24 & 10.3% in 300 Iranian subjects 18 , another study on 2828 Turkish subpopulation had a 6.1% 25 , while martin et al 2018 26 29 . In a micro-Ct Swiss German study on 101 mandibular canines of which 98 single rooted mandibular canines had 7.84% two canals and 3 teeth had two roots 30 , 4.3% in 592 Saudi subpopulation 31 and 2.52% in another 952 Saudi subpopulation 32 , 10.2% in 697 Saudi subpopulation 33 , 15% in 259 north American sub population 21 . 4.9% of 411 Malaysian subpopulation 17 & 9.3% in1702 Malaysian subpopulation 34 .…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 Familiarity with the internal morphology of all the teeth is imperative, as many roots with relatively simple external surfaces, may mask a more complex root canal system. 3 , 4 Therefore, in order to attain effective results, an in-depth understanding and knowledge pertaining to the complexities of the root canal system is necessary. 5 , 6 , 7 , 8 , 9 Moreover, differences regarding the morphologies of root canal system among different populations, races and regions have been well established.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, micro computed tomography (micro-CT) has been shown to provide remarkable visualization and reproduction of internal anatomies and is being considered as gold standard in studies related to root canal morphologies. 4 , 17 However Micro-CT itself is an invasive procedure, appropriate for lab research and therefore not suitable for studies which aim to study differences in root canal morphologies among different genders and ethnicities. 17 Cone beam computed tomography (CBCT) has evolved as an accurate and non-invasive system for 3D assessment of internal morphology of teeth in three planes without the superimposition of anatomical structures.…”
Section: Introductionmentioning
confidence: 99%